A step towards the use of biomonitors as estimators of atmospheric PAHs for regulatory purposes. - Augusto, Sofia; Pereira, Maria J.; Máguas, Cristina; Branquinho, Cristina (Chemosphere, 2013)
One of the main drawbacks of using lichens to monitor atmospheric PAHs has been reported as the inexistence of studies aiming to translate PAH values in lichens into the atmospheric equivalents ones, in order to use this information for regulatory purposes. In this work, PAH concentrations in lichens were compared with PAH concentrations measured in a conventional active sampler in an outdoor environment for a 9-month span. Significant positive correlations between HMW-PAHs, Σ16 EPA-PAHs, and BaP equivalent concentrations in lichens and those in air (TSP) were found. Concentrations of Σ16 EPA-PAHs in lichens and air showed a seasonal variation, with highest values during winter and lowest values during summer. Meteorological variables - temperature, atmospheric pressure, relative humidity, and wind speed - showed to significantly influence PAH concentrations in both lichens and air. Based on the significant linear correlations, equations for translating PAH concentrations measured in lichens into equivalent ones for air were proposed for the first time, allowing a broader use of lichens' information regarding PAHs in monitoring schemes and decision-making.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23668962
Keywords: Air; BaP; Biomonitors; Environment; Human health; PAHs

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - Garcia-Martin, G.; Fernandez-Galiano, E.; Mauri, P. V.; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
The following values have no corresponding Zotero field: periodical: II Congreso Forestal Español pub-location: Pamplona
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos

Multiplicación vegetativa de alcornoque mediante embriogénesis somática. - GARCÍA-MARTÍN, G; Fernandez-Galiano, E; Mauri, P V; Somática, Embriogénesis (II Congreso Forestal Español, 1997)
In order to obtain cork oak clones from selected individuals, somatic embryogenesis was induced in leaves. Somatic embryos can be continuously subcultured with high proliferation rates. This culture system has sorne limiting factors: low percentage of mature embryos obtained, low rate of shoot emergence during germination and high labour and time consumed. Exogenous addition of ABA (l0-6M) concentration during proliferation increased maturation rateo In the same way addition of. BAP (0,001 mg/l) had a positive effect on shoot production. With the aim to obtain a first approach to automation the best culture media for both culture cycles of maturation in liquid medium were determined.
Keywords: ABA; BaP; Cork oak; germination; liquid culture; maturation; somatic embryos